Exploring the extent of job satisfaction, organisational commitment and self-esteem of lecturers at a university of technology in South Africa - Ngidi, David P.; Ngidi, Sizakele A. (Gender and Behaviour, 2017)
This study examined the extent of Job Satisfaction, Organisational Commitment and Self-esteem of university lecturers in the Faculty of Humanities at one of the Universities of Technology in South Africa. A quantitative design was used in this study. To this end, a questionnaire was used in a survey for collecting data. Spector’s (1997) Job Satisfaction Survey (JSS) was used to measure job satisfaction. Meyer, Allen and Smith's (1993) Organisational Commitment Scale (OCS) was used to measure organisational commitment. Rosenberg’s (1969) Self-Esteem Scale was used to measure self-esteem. The findings revealed that: lecturers differed in the extent of their job satisfaction (x2 = 9.941; df =2; p<0.05); gender and department (x2 = 6.388; df = 2; p<0.05 and x2= 6.037; df = 2; p<0.05 respectively) influenced lecturers’ levels of job satisfaction; lecturers differed in the extent of their organisational commitment (x2 = 15.765; df =2; p<0.05); lecturers differed in the extent of their self-esteem (x2 = 30.765; df =1; p<0.05).
Published Article
Keywords: Affective commitment; Continuance commitment; Job satisfactiont; Normative commitment; Organisational commitment; Self-esteem